An An Analysis of Code Mixing in Windah Basudara's YouTube Livestream - Ayu Diyasefia (Journal of English Teaching and Linguistic Issues (JETLI), 2026)
Abstract is This study explores the phenomenon of code mixing in the YouTube livestreams of Windah Basudara, a prominent Indonesian gaming content creator. Utilizing a qualitative content analysis method, the research examines three livestream videos with high viewership to identify patterns, types, and communicative functions of code mixing. The findings reveal 155 instances of code mixing, categorized into insertion (48.38%), alternation (39.35%), and congruent lexicalization (12.25%), based on Muysken’s (2000) framework. The study shows that code mixing in Windah’s content is a deliberate linguistic strategy to enhance expressiveness, connect with a multicultural audience, and reflect digital fluency. This practice underscores the dynamic and performative nature of bilingual communication in digital media, highlighting how code mixing functions as a tool for identity construction, engagement, and sociolinguistic adaptation.